2018
DOI: 10.1111/ecc.12856
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors exhibit a different relationship between muscle strength and health-related quality of life/fatigue compared to healthy subjects

Abstract: We investigated the difference in relationship between muscle strength and quality of life (QOL)/fatigue in long-term cancer survivors and healthy subjects. Thirty-six cancer survivors and 29 healthy subjects were assessed for body composition and bone status at the calcaneus using the Osteo Sono Assessment Index. Muscle strength was evaluated via handgrip and knee extensor strength. Health-related QOL was assessed using the Medical Outcome Study 36-item Short-Form Health Survey. Fatigue was measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
2
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 38 publications
2
37
2
10
Order By: Relevance
“…A Japanese study, of which more than 75% of the subjects were female, found no relation between muscle strength and fatigue in comparisons of cancer survivors and healthy participants [6]. A crosssectional study of Latin Americans including mainly elder people (mean age was 76 for the sarcopenic participants and 70 for the participants without sarcopenia) also concluded that sarcopenia and fatigue were not associated [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A Japanese study, of which more than 75% of the subjects were female, found no relation between muscle strength and fatigue in comparisons of cancer survivors and healthy participants [6]. A crosssectional study of Latin Americans including mainly elder people (mean age was 76 for the sarcopenic participants and 70 for the participants without sarcopenia) also concluded that sarcopenia and fatigue were not associated [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, skeletal muscle mass has been suggested as a factor related to fatigue in cancer patients, although findings on the association between skeletal muscle mass and fatigue have been inconsistent between studies. Some studies have shown strong association between low skeletal muscle mass and fatigue [14,15], whereas other studies have not found any association [6,16,17].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Morishita et al. () examine muscle strength in long‐term cancer survivors—and confirm it is an important factor in improving quality of life, reinforcing the need to focus not just on cardiovascular fitness in cancer rehabilitation programmes. Travier et al.…”
mentioning
confidence: 99%